KOMUNIKASI INTERPERSONAL PIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN GRAND JATRA HOTEL PEKANBARU - Seli Astilani Sinaga; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Grand Jatra Hotel Pekanbaru is a five-star hotel that competes with two other five-star hotels in providing services and services. Grand Jatra Hotel Pekanbaru certainly does not only offer a variety of facilities that can be offered to consumers such as other five-star hotels but needs to be considered in providing quality services from employees to consumers. At this time, the leadership of the Grand Jatra Hotel Pekanbaru needs to support employees with interpersonal communication between leaders and employees to improve employee performance. Therefore, this paper aims to find out the interpersonal communication of leadership in improving the performance of employees of the Grand Jatra Hotel Pekanbaru, which is seen from the attitude of openness, empathy, positive behavior, support and equality owned by the leadership. This study uses a qualitative method. Informants were selected using a purposive technique. Informants in this study amounted to 6 people, namely 1 leader and 5 employees of the Grand Jatra Hotel Pekanbaru. Data collection is done by observation, interview, and documentation. Data analysis techniques by reducing data, collecting data, presenting data, drawing conclusions and evaluating using data validity checking techniques, namely triangulation. The results showed that the interpersonal communication of the leadership of the employees of the Grand Jatra Hotel Pekanbaru was quite good. The leadership always applies openness, empathy, positive attitude, support and equality in the characteristics of the effectiveness of interpersonal communication with a humanistic perspective in improving the performance of employees of the Grand Jatra Hotel Pekanbaru. Openness is seen from employees who can ask questions to get information and open leadership provides information needed by employees. The topic of discussion when communicating is not only related to work but also about family and employees' past. In empathy, the leader is able to understand the needs of employees related to interests, desires and expectations. Positive behavior is shown by leaders by giving praise or appreciation to employees. Leaders are also able to be able to create a pleasant working atmosphere between them. The form of support provided is the provision of ideas, equipment (work infrastructure requirements), and a conducive environment. The leadership in treating employees not looking at the background and position of employees is a form of leadership equality. The language used by leaders when communicating with employees is informal